2000
DOI: 10.1107/s0108768100009447
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the β form of calcium pyrophosphate tetrahydrate

Abstract: -Ca 2 P 2 O 7 Á4H 2 O is monoclinic, P2 1 /c, a = 12.287 (6), b = 7.511 (3), c = 10.775 (5) A Ê , and = 112.54 (1) . Five of the terminal O atoms from a pyrophosphate group bind to Ca atoms, together with O atoms from three of the water molecules. The fourth H 2 O forms only hydrogen bonds. Both Ca atoms have coordination number 7 and show characteristics between those of a capped octahedron and a pentagonal bipyramid. The analysis of coordination distortions suggests that regularity and volume ef®ciency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 8 publications
3
44
0
Order By: Relevance
“…It is found that the crystal belongs to a monoclinic system with cell parameters as , a =12.287 Å, b= 7.511 Å, c = 10.675 Å and β = 113.57°. The cell parameter data are very closely matching with the values reported by Balić-Žunić et al [15], within the limits of estimated standard deviation. Figure 2 represents the powder XRD pattern with assigned reflections.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…It is found that the crystal belongs to a monoclinic system with cell parameters as , a =12.287 Å, b= 7.511 Å, c = 10.675 Å and β = 113.57°. The cell parameter data are very closely matching with the values reported by Balić-Žunić et al [15], within the limits of estimated standard deviation. Figure 2 represents the powder XRD pattern with assigned reflections.…”
Section: Resultssupporting
confidence: 86%
“…Balić-Žunić et al [15] have determined the crystal structure of CPPT and confirmed that the crystal is having monoclinic system with space group P21/c and the cell parameters were, a= 12.287 Å, b= 7.511 Å and c= 10.677 Å and β = 112.57°. Balić-Žunić et al [15] have carried out the detailed crystal structure study of the β form of CPPT.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…CPPD exists in two forms: triclinic and monoclinic, generally abbreviated to t-CPPD and m-CPPD, respectively. A tetrahydrate also exists and is dimorphic, denoted m-CPPTa and m-CPPTb 16 . Characterisation of these forms in the context of their in vivo prevalence has been focussed primarily on microscopy and X-ray powder diffraction (XRPD) studies 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Characterisation of these forms in the context of their in vivo prevalence has been focussed primarily on microscopy and X-ray powder diffraction (XRPD) studies 17,18 . Crystal structures have been determined for t-CPPD 19 , m-CPPTa 20 and m-CPPTb 16 . In addition, the crystal growth and dissolution kinetics of the calcium pyrophosphate hydrate phases have been investigated 21e25 , as has the dehydration 26 .…”
Section: Introductionmentioning
confidence: 99%